Educar pela pesquisa: as percepções de alunos de graduação sobre as temáticas energia e sustentabilidade em um curso de extensão - FONSECA NETO, Sebastião Nogueira da (Universidade Federal do Pará, 2017)
The main goal of this work was evaluating of the science teach with focus in Science, Technology and Society – STS, through “educate by research”, decision-make can promote the energy and sustainability issues in the amazonic context. The study became relevant when take into consideration that the historic occupation of the Amazon was guided on exploration of the natural resources without necessary planning and prevision of the environmental impacts for use itself. Methodologically, this research fits qualitative paradigm and it consists of action research. The collect information happened over extended course, which was recorded in video, training diaries and textual production of the students, all school students of the variable courses of the Federal University of Pará. The data showed that the elaboration of discourses supported on energy and sustainability issues touch several aspects, such as: environmental dimension, social, ecological, political and cultural. From the performed analysis was found that “educate by research”, like method, it is much more efficient to promote training through STS, because the student changes his condition of receptor to builder of knowledge, learn and disclose his discoveries – indicating that science education can provide a training based on critical awareness, autonomy and knowledge builds for coping of the teaching activity.